Driftless gas proportional scintillation counter pulse analysis using digital processing techniques - Simões, P. C. P. S. (2001)
A driftless gas proportional scintillation counter (GPSC) of simple design, using digital pulse-signature analysis, is described. The digital pulse acquisition and processing techniques are shown to be a simple and effective method to determine pulse time duration and to perform pulse amplitude correction in driftless GPSCs. This technique allows the application of driftless GPSCs to x-ray spectrometry up to 60 keV. Although the pulse throughput achieved by the digital pulse-height analyser in this application is limited to about 2 kHz, total interaction rates above 20 kHz can be tolerated by the detector without significant degradation of the pulse-height distributions obtained. Copyright © 2001 John Wiley & Sons, Ltd.